2022
DOI: 10.1038/s41598-022-10554-9
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of fasudil treatment in the APPswe/PSEN1dE9 transgenic (APP/PS1) mice model of Alzheimer’s disease

Abstract: Alzheimer's disease (AD) is the most common cause of progressive dementia. In the present study, we showed hippocampal tissue transcriptome analysis in APPswe/PSEN1dE9 (APP/PS1, AD model) mice treated with fasudil (ADF) and compared with AD mice treated with saline (ADNS) and wild type mice (WT). The competing endogenous RNA (ceRNA) network was constructed and validated the differential expression of mRNA, lncRNA, miRNA, and circRNA. Our study showed differentially expressed mRNAs (DEMs) between WT and ADNS, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 83 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…Although transcriptome studies have previously been carried out in APP/PS1 AD mice, these studies exhibit some limitations in design that affect their informative value. The latter is mainly related to the combined analysis of sexes [ 37 , 38 , 81 ], the selective analysis of males only [ 41 43 ], an unspecified sex distribution [ 39 , 82 ], analysis of only one brain region [ 37 , 39 , 40 , 43 , 81 ], investigation of no distinct brain region (e.g., cortex in total [ 41 , 42 ] or the analysis of entire brain probes [ 38 ] ( S15 Table in S1 File ). Based on our previous findings on distinct electrophysiological alterations in the APP/PS1 AD model related to sex, age and brain region [ 13 , 14 ], we performed transcriptome studies in the RS cortex and hippocampus of both sexes in WT controls and APP/PS1 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Although transcriptome studies have previously been carried out in APP/PS1 AD mice, these studies exhibit some limitations in design that affect their informative value. The latter is mainly related to the combined analysis of sexes [ 37 , 38 , 81 ], the selective analysis of males only [ 41 43 ], an unspecified sex distribution [ 39 , 82 ], analysis of only one brain region [ 37 , 39 , 40 , 43 , 81 ], investigation of no distinct brain region (e.g., cortex in total [ 41 , 42 ] or the analysis of entire brain probes [ 38 ] ( S15 Table in S1 File ). Based on our previous findings on distinct electrophysiological alterations in the APP/PS1 AD model related to sex, age and brain region [ 13 , 14 ], we performed transcriptome studies in the RS cortex and hippocampus of both sexes in WT controls and APP/PS1 mice.…”
Section: Discussionmentioning
confidence: 99%
“…To date, fasudil, as well as its analogues, are the most investigated ROCK inhibitors. Many studies have shown that the compound improves memory deficits, significantly reduces Aβ and p-tau protein levels, restores cognitive function, reduces oxidative stress, and decreases neuronal apoptosis in the hippocampus [ 111 , 112 , 113 , 114 ].…”
Section: 5-ht 6 R/rocki/rockii As Multitarget Appr...mentioning
confidence: 99%
“…AA consumption is elevated in patients with AD, indicating an excess of AA in the human diet could constitute a risk factor for AD ( Rapoport, 2008 ). In APP/PS1 mice (APPswe/PSEN1dE9 transgenic mice model of AD), transcriptome analysis identified the enriched ACSL4 ( Yan et al, 2022 ), which can be inhibited by tetrahydroxy stilbene glycoside (TSG) ( Gao et al, 2021 ). Besides, N2L, a novel lipoic acid-niacin dimer regulating lipid metabolism with multifunction, was also proved to exert neuroprotective effects by blocking the increase of ACSL4 protein expression ( Peng et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%